ПЕРШІ ПОВОЄННІ ВИБОРИ ДО МІСЦЕВИХ РАД НА ТЕРИТОРІЇ ЗАПОРІЗЬКОЇ ОБЛАСТІ (АНАЛІЗ ДЖЕРЕЛ) (Zaporizhzhia Historical Review, 2021)
In the given article are examined sources for the holding of election to the Regional Council of Zaporozhian region in 1947. The author focuses attention on informational means of sources. The author comes to a conclusion that notwithstanding the fact that sources are somewhat limited they are representational enough.